1991
DOI: 10.1002/art.1780340814
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of collagen‐induced arthritis in rats with a monoclonal antibody against the α/β T cell antigen receptor

Abstract: A monoclonal antibody (MAb) to the alpha/beta T cell receptor (TCR alpha/beta), R73 MAb, completely blocked the induction of collagen-induced arthritis (CIA) in rats when the MAb was administered at the time of immunization with type II collagen. When administered after CIA had begun, the progression of the arthritis was suppressed significantly by R73 MAb treatment. The preventive and suppressive effects of R73 MAb on CIA were associated with the depletion of peripheral blood alpha/beta-positive T cells. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The high level of arthritis activity persisted thereafter, resulting in ankylosis in most of the affected joints. The same doses of H57-597 injected on days 0 and 7, in contrast, provided complete protection against CIA, as previously demonstrated in rat models (15,16). Although these unexpected results would suggest a predominant role of regulatory T cells in established CIA, it was also possible that several cytokines, such as tumor necrosis factor a (TNFa), interferon-y (IFNy), or interleukin-2 (IL-2), might have been released immediately after H57-597 injection, a phenomenon similar to that related to anti-CD3 MAb injection, which in turn caused the exacerbation of arthritis.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The high level of arthritis activity persisted thereafter, resulting in ankylosis in most of the affected joints. The same doses of H57-597 injected on days 0 and 7, in contrast, provided complete protection against CIA, as previously demonstrated in rat models (15,16). Although these unexpected results would suggest a predominant role of regulatory T cells in established CIA, it was also possible that several cytokines, such as tumor necrosis factor a (TNFa), interferon-y (IFNy), or interleukin-2 (IL-2), might have been released immediately after H57-597 injection, a phenomenon similar to that related to anti-CD3 MAb injection, which in turn caused the exacerbation of arthritis.…”
Section: Resultssupporting
confidence: 76%
“…The anti-T cell receptor (anti-TCR) MAb, R73, which recognizes T C R d P on rat T cells, has been used exclusively in rat CIA models and shown to be effective not only at the induction phase, but also at the established phase of CIA (15,16). In contrast, a recent study by Yoshino and Cleland (17) demonstrated that this MAb had no effect on chronic CIA in rats.…”
mentioning
confidence: 99%
“…There is a preponderance of evidence implicating CD4 ϩ T cells as the central mediators of disease induction in arthritis (12). Not only does susceptibility segregate with class II MHC (MHC-II) polymorphism, administration of mAbs in mouse models against TCR␣␤, CD4, and I-A all prevent disease (13)(14)(15). Recent gene array analysis of mouse MECs revealed many gene transcripts that may not be controlled by Aire (16,17).…”
mentioning
confidence: 99%
“…Of primary importance are the class I1 molecules that are encoded within the major histocompatibility complex (RTl), and that bind collagen peptides for presentation to T cells by antigen processing cells (5). Equally important are the non-major histocompatibility complex-encoded (non-MHC-encoded), T cell antigen receptor (TCR) molecules, which dictate the strength of interaction between specific T cells and each of the multiple immunogenic peptide fragments of type 11 collagen (6).…”
mentioning
confidence: 99%